Analisis Determinan Tingkat Kemiskinan Di Provinsi Daerah Istimewa Yogyakarta Tahun 2010-2015 - Septiani, Nunik, Dr. Triyono, SE, M.Si (2017)
This study entitled "analysis of the Determinants of poor Population in Yogyakarta Years 2010-2015". The objective is to analyze the influenceof gross regional domestic product, human development index, shopping areas and unemployment against a population of poor in regency/city Yogyakarta special region. The dependent variable in the form of poor population (KM), while the independent variable in the form of gross regional domestic product (GDP), the human development index (HDI), shopping area (BD) and unemployment (PGR). This study uses secondary data with regression analysis techniques to the data pane. The results showed that the fixed effect model (FEM) is a panel data regression model is most appropriate. Based on a test of the validity of influence or test t, gross regional domestic product, human development index and a negative effect unemployment significantly to the population of poor, while the shopping area has no effect against a significant number of poor population. Based on the test F, gross regional domestic product, human development index, shopping areas and unemployment simultaneously or together have an effect on the number of poor population. The results of the regression output show the adjusted R2 of 0.998092 or 99.81%, then the interpretation is a 99.81% variation variable the number of poor population (KM) can be explained by the variable gross regional domestic product (GDP), the human development index (HDI), shopping area (BD) and unemployment (PGR), and the rest of 0.19% variation variable the number of poor population (KM) are described by other free variables not included in the model. Key words: gross regional domestic product, human development index, shopping areas, the unemployed, the number of poor population, panel data regression